Anteriorly Based Galeo-Pericranial Frontalis Flap: A Novel Application in Secondary Rhinoplasty With Atrophic Skin. Issue 2 (March 2016) - Morovic, Carmen Gloria; Soto, Carolina A.; Vidal, Claudia
Abstract : Background: Nasomaxillary dysplasia (Binder syndrome) and cleft are congenital malformations of the midface. Ideally, the nasal deformity is treated from childhood. This approach leads to the need for several surgeries and revisions until full growth is reached. As a result of multiples procedures, the skin over the nasal dorsum sometimes becomes thin, atrophic and could be strongly attached to underlying grafts. For this setting of patients when another rhinoplasty is required, it becomes a technical challenge. The authors describe their experience in complex secondary rhinoplasty performed in patients with thin atrophic skin using the anteriorly based galeo-pericranial frontalis flap (GPFF) to improve the quality of the covering soft tissue along the whole nose skeleton area. Results: Since 2013, 3 female patients; 2 of them with Binder syndrome and 1 cleft lip/palate patient (average 18 years) with previous rhinoplasty (3–6 procedures) are subjected to secondary rhinoplasty using GPFF turning it over the osteochondral nasal framework. Postoperative follow-up was 3 to 18 months. There were no viability complications of the dorsum skin flap in the immediate postoperative period. At long-term follow-up, a visible improvement of local skin conditions and restoration of the nasal contour was achieved. Conclusions: The anteriorly based GPFF is a well-vascularized versatile flap used extensively in anterior cranial fossa surgery and frontal sinus trauma. Given its known and constant vascular anatomy, this flap is adapted to a new application in complex secondary rhinoplasty, in the presence of atrophic skin with good aesthetic outcomes.